UKURAN DEWAN KOMISARIS DAN PROPORSI DEWAN KOMISARIS INDEPENDEN SEBAGAI DETRMINAN MANAJEMEN LABA - Ariyani Ariyani; Rudi Harianto; Putri Zanufa Sari (STIE Mahardhika, 2018)
This study has the aim to obtain empirical evidence about the size of the board of commissioners and the proportion of independent board of directors as a determinant of earnings management. Data analysis techniques used in this study using software assistance in the form of Eviews, data collection used is by purposive sampling method on the food and beverages industry on the Indonesia Stock Exchange with the 2013-2017 study period. Based on the discussion of the results study can be proved that the size of the board have an influence on earnings management and the proportion of independent commissioners has an influence on earnings management.